Single-chain polymer nanoparticles: Mimic the proteins. (1st June 2015) - Huo, Meng; Wang, Niejun; Fang, Tommy; Sun, Mengzhen; Wei, Yen; Yuan, Jinying
Abstract: With recent development in controlled/"living" polymerization and sequence-specific polymeric architecture design, polymeric materials with accurately designed primary structure can be to some extent designed and prepared. Such development has actuated the design of single chain polymer nanoparticles (SCPNs) with tunable high-order structures from well-defined polymeric precursors. Until now, various synthetic strategies for SCPNs have been proposed and some possible applications, especially protein mimicry, have demonstrated the SCPNs' attracting prospect. After briefly introducing the origin of SCPNs, this feature article reviewed the recent development of SCPNs in terms of different crosslinking strategies as well as their potential applications. Meanwhile, we highlighted some important characterization techniques for SCPNs study. Graphical abstract: Highlights: Controlled/"living" polymerization has actuated the design of single chain polymer nanoparticles (SCPNs). One important application of SCPNs is protein mimicry. The development of SCPNs in terms of different crosslinking strategies and their potential applications were reviewed. The characterization techniques for SCPNs study were summarized.